The Aqueous Extract of Polypodium leucotomos (Fernblock®) Regulates Opsin 3 and Prevents Photooxidation of Melanin Precursors on Skin Cells Exposed to Blue Light Emitted from Digital Devices - Mikel Portillo; Manuel Mataix; Miguel Alonso-Juarranz; Silvia Lorrio; María Villalba; Azahara Rodríguez-Luna; Salvador González (Antioxidants, 2021)
The effects of sun exposure on the skin and specifically those related to pigmentation disorders are well known. It has recently been shown that blue light leads to the induction of oxidative stress and long-lasting pigmentation. The protective effect of an aqueous extract of Polypodium leucotomos (Fernblock®) is known. Our aim was to investigate the action mechanism of Fernblock® against pigmentation induced by blue light from digital devices. Human fibroblasts (HDF) and murine melanocytes (B16-F10) were exposed to artificial blue light (a 400–500 nm LED lamp). Cell viability, mitochondrial morphology, and the expression of the mitogen-activated protein kinase (MAPK) p38, known markers involved in the melanogenesis pathway, were evaluated. The activation of Opsin-3, a membrane protein sensitive to blue light that triggers the activation of the enzyme tyrosinase responsible for melanogenesis in melanocytes, was also analyzed. Our results demonstrated that pretreatment with Fernblock® prevents cell death, alteration of mitochondrial morphology, and phosphorylation of p38 in HDF exposed to blue light. In addition, Fernblock® significantly reduced the activation of Opsin-3 in melanocytes and the photo-oxidation of melanin, preventing its photodegradation. In sum, Fernblock® exerts beneficial effects against the detrimental impact of blue light from digital devices and could prevent early photoaging, while maintaining skin homeostasis.